Degradation of Kilombero Valley Ramsar wetlands in Tanzania. (August 2019) - Munishi, Subira; Jewitt, Graham
Abstract: Changes in population dynamics or climate often results in encroachment on wetlands by vulnerable communities in search of grazing or fertile farming land. This has been the case for the Kilombero Valley, a Ramsar site in Tanzania, where exploitation by the immigrating communities is a concern to both the scientific and local communities. The Kilombero wetlands are rich in biodiversity and a major contributor to the livelihoods of local communities and are also regarded as one of the main bread baskets of the country. Previous research initiatives have focused mainly on biodiversity assessments, with emphasis placed on wildlife population changes, believed to be affected by ongoing anthropogenic activities in the valley. In this study, the land cover changes in the Kilombero Valley were analyzed over a span of 30 years. Fourteen Landsat (ETM and TM) images, covering the years 1975, 1990, 2002, 2009 and 2010, were used to generate land use maps for the study area and were analyzed to provide quantitative assessments of change. Post-classification change detection analysis revealed that there has been an extensive exploitation of natural land cover across the valley through agricultural activities. In 1975, the valley floor was dominated by woodland (42%) and seasonal wetlands (37%). However, this has changed over the years and in 2008, 36% of the valley area was under intensive cultivation and 29% was occupied by a mixture of settlement, grazing, and cultivated areas. Findings show that there is a rapid transformation to agricultural-intensive activities, especially in the wetland area. At least 90% of wetland area originally present in the valley has been converted to other land uses and about 84% of the woodlands that existed in 1975 have been replaced by other land covers. This calls for closer attention to the ongoing degradation of the Kilombero wetlands. Highlights: The Kilombero Valley, a Ramsar Site, has undergone major land cover change in a span of 30 years. At least 60% of the formally seasonally inundated wetland has been converted to cultivated land. The natural Miombo woodland zone, habitat for the wildlife, especially the rare Puku has been largely cleared. Agriculture is responsible for most of the conversion quantified, replacing the natural Miombo woodland and wetland areas.